Occult Hepatitis B Virus Infection in Japanese Chronic Hemodialysis Patients. Issue 3 (21st January 2013) - Nagakawa, Osamu; Miyatomi, Yoshiho; Shigeta, Yasuhiro; Inayama, Emi; Murakami, Kouichi; Sakai, Takehiko; Kouno, Takashi; Masai, Motoyuki; Shirai, Kohji; Yoshida, Toyohiko
Abstract: We investigated the prevalence of occult hepatitis B virus (HBV) infection in Japanese chronic hemodialysis patients. Hemodialysis patients ( n = 1041) were screened for occult HBV. The presence of hepatitis B surface antigen (HBsAg), hepatitis B surface antibody, and hepatitis B core antibody (anti‐HBc) was determined by various chemiluminescent immunoassays. HBV‐DNA was quantified in patients positive for anti‐HBc using quantitative real‐time polymerase chain reaction. Among the 1041 patients, six (0.6%) were HBsAg‐positive and 218 (20.9%) were anti‐HBc‐positive. All HBsAg‐positive patients also tested positive for the presence of HBV DNA. Of 212 HBsAg‐negative and anti‐HBc‐positive patients, three were positive for HBV DNA. Our study showed that the prevalence of occult HBV infection in chronic hemodialysis patients from eastern Japan was 0.3%.